Expression of the Autographa californica nuclear polyhedrosis virus apoptotic suppressor gene p35 in nonpermissive Spodoptera littoralis cells. - Gershburg, E (1997)
Apoptosis was postulated as the main barrier to replication of the Autographa californica nuclear polyhedrosis virus (AcMNPV) in a Spodoptera littoralis SL2 cell line (N. Chejanovsky and E. Gershburg, Virology 209:519-525, 1995). Thus, we hypothesized that the viral apoptotic suppressor gene p35 is either poorly expressed or nonfunctional in AcMNPV-infected SL2 cells. These questions were addressed by first determining the steady-state levels of the p35 product, P35, in AcMNPV-infected SL2 cells. Indeed, very low levels of P35 were found in infected SL2 cells in comparison with those in SF9 cells. Overexpression of p35, in transient-transfection and recombinant-virus infection experiments, inhibited actinomycin D- and AcMNPV-induced apoptosis, as determined by reduced cell blebbing and release of oligonucleosomes and increased cell viability of SL2. However, SL2 budded-virus (BV) titers of a recombinant AcMNPV which highly expressed p35 did not improve significantly. Also, injection of S. littoralis larvae with recombinant and wild-type AcMNPV BVs showed similar 50% lethal doses. These data suggest that apoptosis is not the only impediment to AcMNPV replication in these nonpermissive S. littoralis cells, and probably in S. littoralis larvae, so p35 may not be the only host range determinant in this system.